Solar and Stellar Flares 2016
DOI: 10.1007/978-94-024-0935-2_13
|View full text |Cite
|
Sign up to set email alerts
|

Soft X-Ray Pulsations in Solar Flares

Abstract: The soft X-ray emissions (hν > 1.5 keV) of solar flares come mainly from the bright coronal loops at the highest temperatures normally achieved in the flare process. Their ubiquity has led to their use as a standard measure of flare occurrence and energy, although the overwhelming bulk of the total flare energy goes elsewhere. Recently Dolla et al. (2012, Astrophys. J. Lett. 749 L16) noted quasi-periodic pulsations (QPP) in the soft X-ray signature of the X-class flare SOL2011-02-15, as observed by the standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…In some cases, the QPPs occur in both the rise phase and the gradual (decay) phase of the flare (e.g. Van Doorsselaere et al, 2011;Dolla et al, 2012;Simões, Hudson, and Fletcher, 2015). However, in some cases, the QPPs are restricted to only the rise phase (Jakimiec and Tomczak, 2012, and follow-up works), but in other cases, the QPPs are observed during the decay phase only (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In some cases, the QPPs occur in both the rise phase and the gradual (decay) phase of the flare (e.g. Van Doorsselaere et al, 2011;Dolla et al, 2012;Simões, Hudson, and Fletcher, 2015). However, in some cases, the QPPs are restricted to only the rise phase (Jakimiec and Tomczak, 2012, and follow-up works), but in other cases, the QPPs are observed during the decay phase only (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…in the confidence level above the power law in Fourier space (rather than the confidence above the white noise, as is commonly assumed). This was taken into account by Simões, Hudson, and Fletcher (2015), who performed a large study of 35 flares. They still found with 97.5% confidence that most flares (80% of 35 flares) had significant oscillations, above the red noise level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on RATAN-600 microflare observations, periods of 1.4 and 0.7 s were found in the radio emission intensity and polarization signals, respectively . Simões et al (2015) found that 28 out of 35 researched x-flares showed QPPs. Some authors relate changes in the period with the flare phases.…”
Section: Introductionmentioning
confidence: 99%